1999
DOI: 10.1023/a:1026418831238
|View full text |Cite
|
Sign up to set email alerts
|

Dose-finding study of docetaxel and doxorubicin in first-line treatment of patients with metastatic breast cancer

Abstract: Docetaxel-doxorubicin is feasible, safe and highly active. The incidence of febrile neutropenia without G-CSF requires careful monitoring but is acceptable in this setting. There does not appear to be an increase in the cardiac toxicity of doxorubicin. The recommended doses is either docetaxel 75 mg/m2 and doxorubicin 50 mg/m2 or docetaxel 60 mg/m2 and doxorubicin 60 mg/m2, administered every three weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(50 citation statements)
references
References 18 publications
3
47
0
Order By: Relevance
“…The doses of AD were based on the preliminary recommendations available from the (then unpublished) dose-finding study of this combination in first-line treatment of patients with metastatic breast cancer [14]. The doses of AC were those used in primary chemotherapy studies in breast cancer at that time, both in the USA [16] and UK [17].…”
Section: Chemotherapy Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The doses of AD were based on the preliminary recommendations available from the (then unpublished) dose-finding study of this combination in first-line treatment of patients with metastatic breast cancer [14]. The doses of AC were those used in primary chemotherapy studies in breast cancer at that time, both in the USA [16] and UK [17].…”
Section: Chemotherapy Treatmentmentioning
confidence: 99%
“…At the time of development of this study, docetaxel had been shown to have significant activity in patients with metastatic breast cancer, including those patients with anthracycline-resistant disease [12,13]. The single-agent activity of docetaxel and of the anthracyclines, and the absence of complete cross-resistance between them, provided a rationale to develop these drugs in combination in patients with breast cancer [14]. Furthermore, AD gave superior response rates and time to progression, but not superior OS, compared with AC as first-line chemotherapy in patients with metastatic breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several phase I studies were performed, with combinations including docetaxel and doxorubicin (Misset et al, 1999), docetaxel+doxorubicin+cyclo-phosphamide (Nabholtz et al, 1997), docetaxel and epidoxorubicin (Pagani et al, 1999), docetaxel and cisplatin (Crown et al, 1997), docetaxel and vinorelbine (Fumoleau et al, 1996b), and docetaxel and 5-fluorouracil (Lortholary et al, 1997).…”
Section: Docetaxelmentioning
confidence: 99%
“…These data and those of comparable series suggest that the combination of epirubicin and docetaxel is tolerable and active, and that it should be further developed clinically. The Oncologist 2001;6(suppl 3): [13][14][15][16] The Oncologist 2001;6(suppl 3):13-16 www.TheOncologist.com Correspondence: Cristiana Sessa, M.D., Oncology Institute of Southern Switzerland, Ospedale San Giovanni, Bellinzona CH-6500, Switzerland. Telephone: 41-91-820-90-39; Fax: 41-91-820-90-44; e-mail: csessa@ticino.com Received February 6, 2001; accepted for publication March 5, 2001.…”
Section: Introductionmentioning
confidence: 99%
“…This followed publication of data suggesting that the administration of paclitaxel in patients with a greater than 360 mg/m 2 cumulative exposure to doxorubicin might result in a 20% or greater incidence of congestive heart failure [9][10][11][12]. However, with the docetaxel/anthracycline combination, docetaxel did not appear to increase the incidence or severity of cardiotoxicity observed with doxorubicin alone [6,8,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%